Microbial biomass process technologies and management - Behera, Basanta Kumara ; Varma, A. (Springer, 2020)
This book describes how microbes can be used as effective and sustainable resources to meet the current challenge of finding suitable and economical solutions for biopharmaceuticals, enzymes, food additives, nutraceuticals, value added biochemicals and microbial fuels, and discusses various aspects of microbial regulatory activity and its applications. It particularly focuses on the design, layout and other relevant issues in industrial microbe applications. Moreover, it discusses the entire microbial-product supply chain, from manufacturing sites to end users, both in domestic and international markets, providing insights into the global marketing of microbes and microbial biomass-derived products. Further, it includes topics concerning the effective production and utilization of eco-friendly biotechnology industries. It offers a valuable, ready-to-use guide for technologists and policymakers developing new biotechnologies.Foreword; Preface; About the Book; Contents; About the Authors; Abbreviations; Chapter 1: Concept of Microbiological Processes; 1.1 History of Microbial Processes; 1.2 Need for Standard Microbial Processes; 1.3 Microbes and Microbial Products; 1.3.1 Fungi; 1.3.2 Bacteria; 1.3.3 Algae; 1.4 Microbial Process Economics; 1.4.1 What Is Microbial Process Economics; 1.4.2 The Economic Nature of Microbial Processes; 1.4.3 Feedstock; 1.4.3.1 Biocatalysts; 1.4.3.2 Bioenergy; 1.4.3.3 Target-Oriented Product; 1.4.3.4 Microbiological Waste; 1.4.3.5 Interactions.